A Framework for Flexible Sensor Information Dissemination - Corujo, Daniel (2011)
The integration of the digital world into every aspect of our lives is becoming more and more preeminent. Nowadays, not only humans but also devices and the environments where we dwell are also able to provide their own information, through the usage of sensors. Through their interconnection over communication networks, sensors enable Ambient Intelligent scenarios achieving a true Internet of Things, and crossing the gap between computer systems and the real world. However, the different sensing devices and information generated by them, are of such disparate nature that it becomes increasingly difficult to access and make use of such heterogeneous data. In this paper, we propose a framework which not only considers a media independent information access to sensors and their supplied data, but is also flexible enough to configure and provide different means to best transport collected sensor information via wireless gateways, facilitating its deployment in different scenarios. We demonstrate its usefulness by providing a throughput efficient approach towards the collection and dissemination of sensing data, through sensing information compression and aggregation of multiple sources.